FAKTOR-FAKTOR YANG MEMPENGARUHI POLA TIDUR PADA ANAK YANG MENJALANI HOSPITALISASI DI RUANG RAWAT INAP ANAK RSD. MAYJEND. HM. RYACUDU KOTABUMI TAHUN 2016 - Rina Mariani (LPPM Universitas Abdurrab, 2019)
ABSTRACT Problems faced by children during home care is difficulty sleeping due to treatment and environmental conditions that are different from home conditions. Based on a survey conducted in February 2016, out of 12 treated children had difficulty falling asleep due to the disease 's illness and the uncomfortable environment. The purpose of this study was to determine the factors that influence the sleep patterns of children who underwent hospitalization at the inpatient ward of Mayor Jendral HM Ryacudu Kotabumi Regional Hospital. The research design uses quantitative analytic with cross sectional approach. Research sample is children aged 1-3 years amounted to 68 people. The research variables consist of independent and dependent variable. Independent variables are physical illness, environmental and emotional stress while dependent variable is sleep pattern. Data analysis using univariate and bivariate analysis through chi-square test with α = 0,05. The univariate result was obtained by 51 people (75.0%) of disturbed sleep patterns, 48 ​​people (70.6%) had physical illness, 59 people (86.8%) felt the environment was disturbing, and 59 people (86.8%) experienced emotional stress. Bivariate results show there is a relationship between physical illness with sleep patterns in children, there is a relationship between the environment with sleep patterns of children and there is no relationship between emotional stress with sleep patterns in children. Keyword: sleep patterns, children, hospitalization, hospital, difficulty sleeping ABSTRAK Persoalan yang dihadapi anak selama di rawat di rumah adalah kesulitan tidur akibat pengobatan dan keadaan lingkungan yang berbeda dengan kondisi rumah. Berdasarkan presurvey yang dilakukan pada bulan Februari 2016, dari 12 anak yang dirawat mengalami sulit tidur karena`faktor penyakit yang diderita dan lingkungan yang kurang nyaman. Tujuan penelitian adalah untuk mengetahui faktor-faktor yang mempengaruhi pola tidur anak yang menjalani hospitalisasi di ruang rawat inap anak Rumah Sakit Daerah Mayor Jendral HM Ryacudu Kotabumi. Desain penelitian mengunakan analitik kuantitatif dengan pendekatan cross sectional. Sampel penelitian adalah anak usia 1-3 tahun berjumlah 68 orang. Variabel penelitian terdiri atas variabel independen dan dependen. Variabel independen adalah penyakit fisik, lingkungan dan stress emosional sedangkan variabel dependen adalah pola tidur. Analisa data menggunakan analisa univariat dan bivariat melalui uji chi-square dengan α = 0,05. Hasil univariat diperoleh 51 orang (75.0%) pola tidur anak terganggu, 48 orang (70.6%) mengalami penyakit fisik, 59 orang (86.8%) merasakan lingkungan menganggu, dan 59 orang (86.8%) mengalami stress emosional. Hasil bivariat menunjukkan ada hubungan antara penyakit fisik dengan pola tidur pada anak, ada hubungan antara lingkungan dengan pola tidur anak dan tidak ada hubungan antara stress emosional dengan pola tidur pada anak. Kata Kunci: pola tidur, anak, hospitalisasi, rumah sakit, sulit tidur